Movement Technologies, Scale Structure and Metropolitan Life – an Empirical Research on the Effects of the Transportation System on the Metropolitan Process in Beijing - Qiang Sheng; Linfei Han (Footprint)
This paper is a morphological study on Beijing’s metropolitanisation process based on the development of its transportation networks. By extracting the ‘scale structure’ embedded in them, we construct a movement network model for Beijing and use it to analyse changing metropolitan centralities as shopping areas and market places in 1924, 1987 and 2006. Following Taylor’s proposal of Central Flow as a complementary model to Central Place, our study focuses on how the spatial distribution of metropolitan centralities has been affected by the rapid modernisation of transportation networks.